Perubahan Praktik Pertanian: Dokumentasi Pengetahuan Lokal Bertani Tambak di Desa Surodadi yang Mulai Ditinggalkan - Adinda Rizky Awalia; Fajar Fajar (Laboratory of Anthropology Department, Faculty of Humanity, Halu Oleo University, 2025)
Pond farming is an important part of the life of the Surodadi Village community. In the past, farming practices were carried out with several stages that were local wisdom and carried out several traditions. Over time, local wisdom practices and traditions began to be abandoned by farmers and now a new way of farming is formed. This study aims to determine the old farming practices that are local wisdom, factors causing the abandonment of old practices, and new forms of farming practices. The method used in this research is a qualitative method with a qualitative descriptive approach. Data collection was done through observation, interviews and documentation. Interviews were conducted with the village head as a key informant, 4 main informants namely 2 old and 2 young pond farmers, and 2 family members of pond farmers as supporting informants. Data validity techniques used in this research are source triangulation and technique triangulation using Milles and Huberman techniques. The theory used to analyze changes in agricultural practices in Surodadi Village is Talcott Parsons' social system theory. The results of this study indicate that old pond farming practices in Surodadi Village use a series of practices that are local wisdom and also utilize natural resources wisely and environmentally friendly in practice. Some series of pond farming practices that are local wisdom began to be abandoned by the community. 2 factors that influence changes in pond farming practices are environmental and economic changes. Environmental changes that cause environmental degradation make a new form of pond farming practices in Surodadi Village.